2019
DOI: 10.1177/0265407519826743
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how exchange orientation affects conflict and intimacy in the daily life of romantic couples

Abstract: We test the hypothesis that partners’ tendency to “keep score” in a relationship—as reflected in their exchange orientation—will moderate the effect of daily conflicts on their relationship evaluations. Cohabitating romantic partners ( N = 82 couples) participated in a 28-day daily diary study. Partners higher in exchange orientation showed lower intimacy with their partner on days with conflict compared to days without conflict; the effect was attenuated for partners lower in exchange orientation. This result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Exchange orientation was assessed with a 9-item exchange orientation scale developed by Clark et al (1987). However, as exchange orientation can also be considered a general orientation and to vary with specific relationships, the Likert-type scale was adapted to reference the participant’s spouse following Jarvis et al (2019). An example item is, “When I give something to my partner, I generally expect something in return.” Anchor points were 1 = Strongly Disagree to 7 = Strongly Agree .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exchange orientation was assessed with a 9-item exchange orientation scale developed by Clark et al (1987). However, as exchange orientation can also be considered a general orientation and to vary with specific relationships, the Likert-type scale was adapted to reference the participant’s spouse following Jarvis et al (2019). An example item is, “When I give something to my partner, I generally expect something in return.” Anchor points were 1 = Strongly Disagree to 7 = Strongly Agree .…”
Section: Methodsmentioning
confidence: 99%
“…Having higher levels of exchange orientation (i.e., keeping score) should have negative effects on intimate relationships (Clark & Waddell, 1985). Lending credence to the idea that exchange orientations are problematic for romantic partners, Jarvis et al (2019) explored targeted partner-specific exchange orientation (rather than a general exchange orientation) in association with couples’ degree of conflict. They found that, while exchange orientation was not associated with frequency of conflict, it did appear to increase the negative effect of conflict on intimacy.…”
Section: Relational Orientationsmentioning
confidence: 99%
“…Between-family dispositional characteristics have recently attracted empirical attention as candidate features of family life that may explain between-family heterogeneity in within-family dynamics (e.g., Fosco & Lydon-Staley, 2019;Jarvis, McClure, & Bolger, 2019). The dyadic patterns of marital conflict that characterize a family across years (Gottman, 1993;Whitton et al, 2018), may be one reason for between-family differences in within-family associations between marital conflict and mother-adolescent conflict.…”
Section: Marital Conflict Patterns and Heterogeneity In Within-familymentioning
confidence: 99%
“…Between‐family dispositional characteristics have recently attracted empirical attention as candidate features of family life that may explain between‐family heterogeneity in within‐family dynamics (Fosco & Lydon‐Staley, 2019 ; Jarvis, McClure, & Bolger, 2019 ). The dyadic patterns of marital conflict that characterize a family across years (Gottman, 1993 ; Whitton et al., 2018 ), may be one reason for between‐family differences in within‐family associations between marital conflict and mother–adolescent conflict.…”
Section: Marital Conflict Patterns and Heterogeneity In Within‐family...mentioning
confidence: 99%